2018
DOI: 10.5125/jkaoms.2018.44.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Role of E-cadherin and cyclin D1 as predictive markers of aggression and clonal expansion in head and neck squamous cell carcinoma

Abstract: ObjectivesHead and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Inconsistency in various histopathologic features for predicting nodal metastasis and overall prognosis and a better understanding of molecular mechanisms of tumourigenesis have shifted the focus to a search for more definitive predictive markers. To identify the role of two immunohistochemical (IHC) markers, E-cadherin and cyclin D1, as predictive markers of aggressiveness in HNSCC and to assess clonal expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…However, cyclin A is the only cyclin that exhibits a statistical difference between poorly differentiated and moderately differentiated cSCC with PNI (p = 0.0277). In contrast to other studies showing overexpression of cyclin D1 in SCC, we found no significant differences in cyclin D1 expression [37][38][39]. One possible explanation could be due to the fact that A431 and Pam 212 tumors potentially exhibit overexpression of different isoforms of cyclin D [40].…”
Section: Plos Onecontrasting
confidence: 99%
“…However, cyclin A is the only cyclin that exhibits a statistical difference between poorly differentiated and moderately differentiated cSCC with PNI (p = 0.0277). In contrast to other studies showing overexpression of cyclin D1 in SCC, we found no significant differences in cyclin D1 expression [37][38][39]. One possible explanation could be due to the fact that A431 and Pam 212 tumors potentially exhibit overexpression of different isoforms of cyclin D [40].…”
Section: Plos Onecontrasting
confidence: 99%
“…E-cadherin expression is recognized to play a crucial role in the suppression of breast tumors such as head and neck squamous cell carcinoma aggressive cancers. The loss of E-cadherin may cause tumors to become more aggressive and increase their invasion ability and metastasis [ 31 ]. However, Nieman et al [ 32 ] showed that N-cadherin contributes motility of human BC cells regardless of their expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the lower E-cadherin expression is associated with several gene mutations. 11 Function changes of E-cadherin occur due to missense mutations in ovarian cancer. Ecadherin gene mutations are also found in diffuse gastric cancer with a percentage of 30%.…”
Section: Discussionmentioning
confidence: 99%